The Role of Time Perspective, Motivation, Attitude, and Preparation in Educational Choice and Study Progress. (24th November 2016) - Slijper, Jeany; Kunnen, E. Saskia; Onstenk, Jeroen; van Geert, Paul
Abstract : The present study examined the relation between study progress in the first year of education and different aspects of the process of study choice of 89 students of higher professional education. This study consists of three parts. Firstly, we explored which concepts are important in open interviews concerning choice of study and study progress. Secondly, we examined the relations between future time perspective and motivation on the one hand and study success on the other hand. Students who focus on the here and now generally continued their studies while students focusing on the future and the ulterior profession, presenting an extended future time perspective, drop out more frequently. Intrinsic motivation is strongly related to positive study progress, and extrinsic controlled motivation is strongly related to dropout. Extrinsic autonomous motivation is in between. Furthermore, students' attitudes towards their future studies were examined in relation to their study progress. The results show that students with an attitude characterized by doubt have the highest risk to drop out. Finally, comparing different orientation programs, we show that students who prepare themselves more intensively before making their choice show less dropout.